2013
DOI: 10.1038/jid.2012.364
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Structural Support of the Dermal Microenvironment Activates Fibroblasts, Endothelial Cells, and Keratinocytes in Aged Human Skin In Vivo

Abstract: The dermal extracellular matrix (ECM) provides strength and resiliency to skin. The ECM consists mostly of type I collagen fibrils, which are produced by fibroblasts. Binding of fibroblasts to collagen fibrils generates mechanical forces, which regulate cellular morphology and function. With aging, collagen fragmentation reduces fibroblast-ECM binding and mechanical forces, resulting in fibroblast shrinkage and reduced function including collagen production. Here, we report that these age-related alterations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
165
0
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 195 publications
(181 citation statements)
references
References 56 publications
9
165
0
7
Order By: Relevance
“…Importantly, TβRII expression is also reduced in aged skin (Quan et al ., 2006; Quan & Fisher, 2015), suggesting that impaired TGF‐β signaling may be a key mediator of reduced ECM production. This possibility is supported by recent evidence demonstrating that ECM production can be significantly stimulated in aged human skin by enhancing structural support of the dermis with injectable cross‐linked hyaluronic acid dermal filler (Quan et al ., 2013b). Localized increase in mechanical force causes fibroblasts in proximity to the filer to enlarge and up‐regulate TβRII expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, TβRII expression is also reduced in aged skin (Quan et al ., 2006; Quan & Fisher, 2015), suggesting that impaired TGF‐β signaling may be a key mediator of reduced ECM production. This possibility is supported by recent evidence demonstrating that ECM production can be significantly stimulated in aged human skin by enhancing structural support of the dermis with injectable cross‐linked hyaluronic acid dermal filler (Quan et al ., 2013b). Localized increase in mechanical force causes fibroblasts in proximity to the filer to enlarge and up‐regulate TβRII expression.…”
Section: Discussionmentioning
confidence: 99%
“…Skin samples were 4 mm in diameter, full thickness skin. As previously described (Quan et al ., 2013b), approximately 200 fibroblasts from each cryosection (15 μm) were collected in lysis buffer (RNeasy Micro kit, Qiagen, Chatsworth, CA, USA), followed by RNA extraction and RT–PCR, as described above. All procedures involving human subjects were approved by the University of Michigan Institutional Review Board, and all subjects provided written informed consent.…”
Section: Methodsmentioning
confidence: 99%
“…In this state, the ECM microenvironment is unable to provide sufficient mechanical stability to maintain normal cell spreading/mechanical force [7,20,27]. Therefore, age-related fragmentation of the collagen fibrils deleteriously alters fibroblast size/mechanical tension and function associated with skin connective tissue aging [7,27,28]. Reduced fibroblasts size stimulates intracellular ROS generation.…”
Section: Collagen Fragmentation Collapses Dermal Fibroblasts and Incrmentioning
confidence: 99%
“…This regeneration occurs because BVG contains high levels of HA (Shiedlin et al 2004). Indeed, previous a study showed that HA could enhance fibroblast extracellular structural mechanical supports, change fibroblast cellular morphologies, re-expose of hidden TGF-β1 receptor and ameliorate the TGF-β1 signaling pathway in procollagen synthesis (Quan et al 2013). As well known previously, binding TGF-β1 on its receptor may stimulate procollagen synthesis through smad 3 activation.…”
Section: Discussionmentioning
confidence: 74%
“…This change occurs due to cross-linking between hyaluronic acid and collagen fibrils, which can reinforce fibroblast extracellular mechanical support, change fibroblast cellular morphologies, and ultimately ameliorate the TGF-β1 signaling pathway (Quan et al 2013). This in vitro result is parallel with clinical findings where treatment with a hyaluronic regenerative matrix indicate significantly acceleration in healing of chronic ulcers (Motolese et al 2013).…”
mentioning
confidence: 99%